SPE International Oilfield Scale Conference and Exhibition 2014
DOI: 10.2118/169751-ms
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Stoichiometry, and Modelling of Mixed Calcium Magnesium Phosphonate Scale Inhibitor Complexes for Application in Precipitation Squeeze Processes

Abstract: In this paper, the properties of precipitated "mixed" calcium and magnesium phosphonate scale inhibitor (SI) complexes formed by 9 common phosphonate species are investigated. These complexes are of the form SI_ Ca Nl _Mg N2 where the stoichiometry (Ca 2ϩ /SI and Mg 2ϩ /SI molar ratios, i.e. N 1 and N 2 ) in various precipitates are established experimentally, and the effect of solution pH on the stoichiometry is determined. Static precipitation tests were performed varying the amounts of Ca 2ϩ and Mg 2ϩ prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Interestingly, when PPCA was tested with EDTMPA ( Figure 16), only the 2 hour IE was enhanced marginally, whereas the 22 hour synergistic IE was lower than the individual EDTMPA IE. These observations are most likely indicative of the predominant mechanism by which PPCA operates, which is probably mainly by nucleation inhibition, although PPCA is still capable of some crystal growth inhibition properties, as stated in the literature (Boak, 2013;Sorbie and Laing, 2004;Sorbie et al, 2000;Shaw and Sorbie, 2013c;Yuan et al, 1998). Generally, most polymers function mainly by nucleation inhibition, and this results in 2 hour IE often being significantly better than their long-term IE (e.g.…”
Section: Spe-169752-msmentioning
confidence: 60%
See 4 more Smart Citations
“…Interestingly, when PPCA was tested with EDTMPA ( Figure 16), only the 2 hour IE was enhanced marginally, whereas the 22 hour synergistic IE was lower than the individual EDTMPA IE. These observations are most likely indicative of the predominant mechanism by which PPCA operates, which is probably mainly by nucleation inhibition, although PPCA is still capable of some crystal growth inhibition properties, as stated in the literature (Boak, 2013;Sorbie and Laing, 2004;Sorbie et al, 2000;Shaw and Sorbie, 2013c;Yuan et al, 1998). Generally, most polymers function mainly by nucleation inhibition, and this results in 2 hour IE often being significantly better than their long-term IE (e.g.…”
Section: Spe-169752-msmentioning
confidence: 60%
“…Presumably this is because the mechanistic benefits of both inhibitors are exploited in the synergistic tests. For example, earlier basic IE tests have shown that DETPMP is more efficient than HMTPMP at 22 hours (Shaw et al, 2012a) because DETPMP is probably a better crystal growth blocker (Sorbie et al, 2000;Sorbie and Laing, 2004;Yuan et al, 1998). In some cases, HMTPMP has been shown to be more efficient than DETPMP at 2 hours, particularly in higher [Ca 2ϩ ] brine mixes (Shaw, 2012;Shaw et al, 2012a) and hence HMTPMP may be a better nucleation inhibitor than DETPMP, which may be related to the HMTPMP chemical structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations